Vínculos artísticos entre España y Perú (1892-1929): elementos para la construcción del imaginario nacional peruano - Villegas Torres, Fernando (2013)
The present study examines the connection between Spanish and Peruvian art, primarily painting and sculpture, between the years 1892 and 1929. The initial year was chosen specifically because right at that time a number of Peruvian painters belonging to the so-called “second generation” received their academic training in Europe (Paris and Madrid). We refer to artists like Carlos Baca Flor, Luis Astete y Concha, Daniel Hernández and Teófilo Castillo. The final year of our investigation saw the construction of the Peruvian Pavillion at the Exposición Iberoamericana in Seville, which can be understood as a kind of culmination of the artistic period under discussion. This exhibition, in which all Latin American nations participated, was the ultimate expression of the intricate cultural and economic relationships Spain still maintained with its former viceroyalties. The global economic crisis of 1929 and the Spanish Civil War in its aftermath put an abrupt end to this process of rapprochement.